O desenvolvimento das unidades curriculares eletivas do campo do conhecimento biológico numa escola de ensino médio em tempo integral do estado do Ceará - Almeida, Adriana de Sousa (2023)
This dissertation was developed within the scope of the Professional Master's Degree in Science and Mathematics Teaching (ENCIMA) of the Federal University of Ceará (UFC) and had as its general objective to analyze how teachers in the area of Natural Sciences and its technologies, and especially Biology, of a Full-Time High School develop the work with the Elective Curricular Units in the perspective of diversifying the teaching of Biology, followed by the specific objectives: to present the trajectory of implementation of Full-Time Schools in Brazil, with emphasis on the state of Ceará; analyze the differentiated curriculum of the FullTime High Schools of this State; know the main Elective Curricular Units taught by the teachers of Biology and the area of Natural Sciences; analyze the development of the work of teachers with the Elective Curricular Units and identify if the Elective Curricular Units contribute to students building their training itineraries focused on the field of biological knowledge. In order to achieve the proposed objectives, a qualitative research was used as a methodology, which was based on the methodology of a case study, based mainly on the concepts of Biology teaching, integral education, full-time education schools, curriculum and Elective Curricular Units. For data collection, techniques of analysis of official documents, participant observation, application of a questionnaire and a semi-structured interview with 5 (five) professors who teach the Elective Curricular Units in the areas of Natural Sciences, linked to the field of biological knowledge, were used. The result of the analyses indicated that the Elective Curricular Units contribute significantly to the students and also to the teachers themselves, evaluating that they have provided them with opportunities to work on the subjects in a more comprehensive and detailed way, however, there are still difficulties to teach these electives, especially with the lack of support material, adequate facilities and the lack of interest of students. In view of this, it is important to seek to improve their development and planning in order to be able to offer an education that contributes to the development of essential skills for human emancipation, sociability and academic success.